2017
DOI: 10.3126/banko.v27i1.18545
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of snow leopard (Panthera uncia) and its wild prey in Chhekampar VDC, Manaslu Conservation Area, Nepal

Abstract: Snow leopard (Panthera uncia) is the striking symbol as well as an indicator of intact eco-regions of high mountains it inhabits. Despite the advancement in new methods, scholars argue that signs are still a reliable indicator for the purpose of habitat use study of snow leopards. The relative abundance of snow leopard and its major prey species such as blue sheep (Pseudois nayar) and Himalayan tahr (Hemitragus jemlahicus) in the Chhekampar Village Development Committee within the Tsum Valley of the Manaslu Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…We applied total counts which, apart from producing such minimum density estimates, are also cost-effective and reliable for the analysis of population trends in mountain ungulates (Largo et al, 2008;Loison et al, 2006). Our result (6.0-7.7 individuals/km 2 in spring and 6.9-7.8 individuals/km 2 in autumn) is similar to previously reported densities in the Manang area both before and after the official establishment of the Annapurna Conservation Area (before: 6.6-10.2 individuals/ km 2 ; Sherpa & Oli, 1988cited in Oli, 1991Wegge & Oli, 1988cited in Oli, 1991Oli, 1994;after: 6.3-9.4 Wilson, 1981), Manaslu Conservation Area (Devkota et al, 2017), Api Nampa Conservation Area (Khanal et al, 2020), Kangchenjunga Conservation Area (Thapa, 2006cited in Khanal et al, 2020, and Shey Phoksundo National Park (Thapa, 2006 cited in Khanal et al, 2020). The studies outside of Nepal reported 0.7-7.1 individuals/km 2 in Bhutan (Wangchuck Centennial National Park, TA B L E 1 Summary of generalized additive models (GAMs) describing habitat selection by blue sheep in Manang based on direct observations in spring and autumn.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We applied total counts which, apart from producing such minimum density estimates, are also cost-effective and reliable for the analysis of population trends in mountain ungulates (Largo et al, 2008;Loison et al, 2006). Our result (6.0-7.7 individuals/km 2 in spring and 6.9-7.8 individuals/km 2 in autumn) is similar to previously reported densities in the Manang area both before and after the official establishment of the Annapurna Conservation Area (before: 6.6-10.2 individuals/ km 2 ; Sherpa & Oli, 1988cited in Oli, 1991Wegge & Oli, 1988cited in Oli, 1991Oli, 1994;after: 6.3-9.4 Wilson, 1981), Manaslu Conservation Area (Devkota et al, 2017), Api Nampa Conservation Area (Khanal et al, 2020), Kangchenjunga Conservation Area (Thapa, 2006cited in Khanal et al, 2020, and Shey Phoksundo National Park (Thapa, 2006 cited in Khanal et al, 2020). The studies outside of Nepal reported 0.7-7.1 individuals/km 2 in Bhutan (Wangchuck Centennial National Park, TA B L E 1 Summary of generalized additive models (GAMs) describing habitat selection by blue sheep in Manang based on direct observations in spring and autumn.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, in other parts of the Nepalese Himalaya the minimum densities were estimated as 0.5–4.2 individuals/km 2 in Upper Mustang in the Annapurna Conservation Area (Aryal et al., 2014b; WWF Nepal, 2013; R.P. Lama & M. Filla, unpublished data), Dhorpatan Hunting Reserve (Aryal et al., 2010; Wilson, 1981), Manaslu Conservation Area (Devkota et al., 2017), Api Nampa Conservation Area (Khanal et al., 2020), Kangchenjunga Conservation Area (Thapa, 2006 cited in Khanal et al., 2020), and Shey Phoksundo National Park (Thapa, 2006 cited in Khanal et al., 2020). The studies outside of Nepal reported 0.7–7.1 individuals/km 2 in Bhutan (Wangchuck Centennial National Park, Shrestha et al, 2012 cited in Leki et al., 2018), India (Ladakh region, Fox et al., 1991; Spiti region, Mishra et al., 2004), and China (Qinghai and Gansu Provinces, Schaller et al., 1988; Helan Mountains, Wang et al., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…We recorded snow leopard presence in five of the six blocks surveyed. Although the rate at which we encountered snow leopard signs (1.9/km for all blocks combined) was lower than reported in other protected areas of Nepal (Kanchenjunga Conservation Area: 5.4 signs/km, Thapa, 2006; Sargarmatha National Park: 4.2 signs/km, Ale et al, 2007; Annapurna Conservation Area: 5.8 signs/km, Ale et al, 2014; Manaslu Conservation Area: 3.5 signs/km, Devkota et al, 2017), the prey biomass was sufficiently large to support a breeding population of snow leopards. Survey times may influence sign encounter rate.…”
Section: Discussionmentioning
confidence: 61%
“…There may be a higher detection rate in winter and post-winter because of accumulation of snow and minimal human presence (Jackson & Hunter, 1996). Devkota et al (2017), for example, surveyed both pre-winter (November–December) and post-winter (May–April). Our surveys, however, were conducted just after the migratory livestock grazing and fungal caterpillar collection season (October–November).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation